2017
DOI: 10.1002/ijgo.12398
|View full text |Cite
|
Sign up to set email alerts
|

Negotiating quality standards for effective delivery of labor and childbirth care in Nigeria and Uganda

Abstract: Objective: "Negotiated standards" describe a level of quality of care that is acceptable and achievable within a specific health system, based on consensus between key stakeholders. This paper presents the development of negotiated standards for effective labor and childbirth care in selected hospitals and communities in Nigeria and Uganda.Methods: A four-step development process involving different methodologies. The process included: (1) review and synthesis of internationally recognized intrapartum clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 16 publications
1
22
0
Order By: Relevance
“…The pain that women experience is influenced by both physiological and psychological processes, including the way in which labor is managed, birthing positions, and mobility during labor . During a dissemination workshop, we asked women in both Nigeria and Uganda about their expectations regarding pain management during labor and childbirth, and most were unaware of measures that could be taken to alleviate pain . Similarly, a survey of maternity care providers in Nigeria concluded that providers had a positive attitude toward pain relief during labor, but gaps existed between provider attitudes and the provision of pain relief during labor .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The pain that women experience is influenced by both physiological and psychological processes, including the way in which labor is managed, birthing positions, and mobility during labor . During a dissemination workshop, we asked women in both Nigeria and Uganda about their expectations regarding pain management during labor and childbirth, and most were unaware of measures that could be taken to alleviate pain . Similarly, a survey of maternity care providers in Nigeria concluded that providers had a positive attitude toward pain relief during labor, but gaps existed between provider attitudes and the provision of pain relief during labor .…”
Section: Discussionmentioning
confidence: 99%
“…Participants received the equivalent of approximately USD $10 to compensate for transportation costs. No additional contact with research participants occurred after data collection, but preliminary results were presented to community members for feedback during a process of developing negotiated standards of care . Transcription and translation occurred in parallel to data collection and field notes were integrated into transcripts.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Having found out what mattered to stakeholders locally, the next step was to translate these views into a set of agreed quality standards, as presented in Oladapo et al 13 Translation of qualitative insights into clear standards for practice is uncommon. Both the participatory development methods, and the core elements The final and completely unique step in the process was to integrate the collaboratively developed quality standards into locally relevant tools.…”
Section: In 2000 That Integrated Evidence With Values and Skillsmentioning
confidence: 99%
“…Having found out what mattered to stakeholders locally, the next step was to translate these views into a set of agreed quality standards, as presented in Oladapo et al . Translation of qualitative insights into clear standards for practice is uncommon.…”
mentioning
confidence: 99%